Space Debris: il problema dei rifiuti spaziali (GEOmedia, 2008)
Space Debris: the space garbage problemThe dramatic growth in space activities since 1957 has generated a large amount of "in-orbit garbage”, namely space-debris. Many of these are potentially dangerous for space vehicles and/or for the people on Earth. In an acceptable space security framework, amajor role is reserved to cooperative space debris monitoring in order to prevent and to mitigate the effects of the problem.